2020
DOI: 10.1002/brb3.1974
|View full text |Cite
|
Sign up to set email alerts
|

Self‐administered biofeedback treatment app for pediatric migraine: A randomized pilot study

Abstract: Objective To investigate the effect size, safety, and tolerability of a therapist‐independent biofeedback treatment app among adolescent with migraine. Materials and Methods This was a prospective, 3:1 ratio randomized, sham‐controlled, double‐blind, pilot study with 16 adolescents diagnosed with migraine randomized to eight weeks of biofeedback treatment (n = 12) or sham biofeedback (n = 4), carried out at two university hospitals in Norway. The prespecified and primary objective of the study was to observe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Headache disability was assessed in 9 of the 13 studies (69%) 34,37,39,41,44–48 . Specifically, Devineni and Blanchard used an interactive website with therapist support and demonstrated a significant decline in headache disability in the treatment arm compared to the control arm at post‐intervention 39 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Headache disability was assessed in 9 of the 13 studies (69%) 34,37,39,41,44–48 . Specifically, Devineni and Blanchard used an interactive website with therapist support and demonstrated a significant decline in headache disability in the treatment arm compared to the control arm at post‐intervention 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies (n = 7/13; 54%) did not report racial/ethnic composition of the sample. [37][38][39][40][41][42][43] Across studies that reported the racial/ethnic composition of the sample (n = 6), 34,[44][45][46][47] White/Caucasian participants comprised 45-94% of the study samples with two thirds of these studies (n = 4) including a sample that was >75% White/Caucasian. 34,44,45,47 Diagnosis of a primary headache disorder was an inclusion criteria for all studies with 69% (9/13) of these studies focusing exclusively on patients with migraine.…”
Section: Re Sultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies utilizing mindfulness interventions have been reported. In a recent review, Stubberud et al [ 69 ] concluded that “…mindfulness may be an important tool as part of a comprehensive treatment approach to help patients ‘mindfully’ engage in valued life activities.” (p. 217).…”
Section: Biofeedbackmentioning
confidence: 99%